Effective treatment of post-spinal fusion methicillin-resistant Staphylococcus aureus vertebral osteomyelitis with linezolid in a renal-transplant patient. (December 2015) - Yunde, Atsushi; Inage, Kazuhide; Orita, Sumihisa; Yamauchi, Kazuyo; Suzuki, Miyako; Sakuma, Yoshihiro; Kubota, Go; Oikawa, Yasuhiro; Sainoh, Takeshi; Sato, Jun; Fujimoto, Kazuki; Shiga, Yasuhiro; et al.
Abstract Background Methicillin-resistantStaphylococcus aureus (MRSA)-caused pyogenic spondylitis is a serious complication associated with lumbar fusion surgery. Often, anti-MRSA drugs are not used properly or patients discontinue drug use because of side effects including renal failure. Case presentation We report a case at our hospital of a 54-year-old male renal-transplant patient who developed MRSA vertebral osteomyelitis after spinal fusion and was treated effectively with linezolid. After diagnosis of post–fusion surgery osteomyelitis, we conducted emergency flushing and debridement and began linezolid treatment (1200 mg/day, divided) immediately after the surgery. The level of C-reactive protein gradually decreased and became negative 4 weeks after the initiation of linezolid treatment. Serum creatinine level was approximately 1.3 mg/dL throughout the treatment period, indicating no deterioration in renal function. Conclusion These results suggest that early flushing and debridement together with linezolid administration is an effective treatment for MRSA vertebral osteomyelitis in renal-transplant patients.